Mu Opioid Receptor Actions in the Lateral Habenula - Margolis, Elyssa B. (PLoS One, 2016)
Increased activity of lateral habenula (LHb) neurons is correlated with aversive states including pain, opioid abstinence, rodent models of depression, and failure to receive a predicted reward. Agonists at the mu opioid receptor (MOR) are among the most powerful rewarding and pain relieving drugs. Injection of the MOR agonist morphine directly into the habenula produces analgesia, raising the possibility that MOR acts locally within the LHb. Consequently, we examined the synaptic actions of MOR agonists in the LHb using whole cell patch clamp recording. We found that the MOR selective agonist DAMGO inhibits a subset of LHb neurons both directly and by inhibiting glutamate release onto these cells. Paradoxically, DAMGO also presynaptically inhibited GABA release onto most LHb neurons. The behavioral effect of MOR activation will thus depend upon both the level of intrinsic neuronal activity in the LHb and the balance of activity in glutamate and GABA inputs to different LHb neuronal populations.